Total Neoadjuvant Therapy With Short-Course Radiation: US Experience of a Neoadjuvant Rectal Cancer Therapy. Issue 2 (February 2022) - Chapman, William C.; Kim, Hyun; Bauer, Philip; Makhdoom, Bilal A.; Trikalinos, Nikolaos A.; Pedersen, Katrina S.; Glasgow, Sean C.; Mutch, Matthew G.; Silviera, Matthew L.; Roy, Amit; Parikh, Parag J.; Hunt, Steven R.
Abstract : BACKGROUND: Short-course radiation followed by chemotherapy as total neoadjuvant therapy has been investigated primarily in Europe and Australia with increasing global acceptance. There are limited data on this regimen's use in the United States, however, potentially delaying implementation. OBJECTIVE: This study aimed to compare clinical performance and oncologic outcomes of 2 rectal cancer neoadjuvant treatment modalities: short-course total neoadjuvant therapy versus standard chemoradiation. DESIGN: This is a retrospective cohort study. SETTING: This study was performed at a National Cancer Institute-designated cancer center. PATIENTS: A total of 413 patients had locally advanced rectal cancers diagnosed from June 2009 to May 2018 and received either short-course total neoadjuvant therapy or standard chemoradiation. INTERVENTIONS: There were 187 patients treated with short-course total neoadjuvant therapy (5 × 5 Gy radiation followed by consolidation oxaliplatin-based chemotherapy) compared with 226 chemoradiation recipients (approximately 50.4 Gy radiation in 28 fractions with concurrent fluorouracil equivalent). MAIN OUTCOME MEASURES: Primary end points were tumor downstaging, measured by complete response and "low" neoadjuvant rectal score rates, and progression-free survival. Secondary analyses included treatment characteristics and completion, sphincter preservation, and recurrence rates. RESULTS: Short-course total neoadjuvant therapy was associated with higher rates of complete response (26.2% vs 17.3%; p = 0.03) and "low" neoadjuvant rectal scores (40.1% vs 25.7%; p < 0.01) despite a higher burden of node-positive disease (78.6% vs 68.9%; p = 0.03). Short-course recipients also completed trimodal treatment more frequently (88.4% vs 50.4%; p < 0.01) and had fewer months with temporary stomas (4.8 vs 7.0; p < 0.01). Both regimens achieved comparable local control (local recurrence: 2.7% short-course total neoadjuvant therapy vs 2.2% chemoradiation, p = 0.76) and 2-year progression-free survival (88.2% short-course total neoadjuvant therapy (95% CI, 82.9–93.5) vs 85.6% chemoradiation (95% CI, 80.5–90.7)). LIMITATIONS: Retrospective design, unbalanced disease severity, and variable dosing of neoadjuvant consolidation chemotherapy were limitations of this study. CONCLUSIONS: Short-course total neoadjuvant therapy was associated with improved downstaging and similar progression-free survival compared with chemoradiation. These results were achieved with shortened radiation courses, improved treatment completion, and less time with diverting ostomies. Short-course total neoadjuvant therapy is an optimal regimen for locally advanced rectal cancer. See Video Abstract at http://links.lww.com/DCR/B724 . TERAPIA NEOADYUVANTE TOTAL CON RADIACIÓN DE CORTA DURACIÓN: EXPERIENCIA ESTADOUNIDENSE DE UNA TERAPIA NEOADYUVANTE CONTRA EL CÁNCER DE RECTO ANTECEDENTES: La radiación de corta duración seguida de quimioterapia como terapia neoadyuvante total se ha investigado principalmente en Europa y Australia con una aceptación mundial cada vez mayor. Sin embargo, datos limitados sobre el uso de este régimen en los Estados Unidos, han potencialmente retrasando su implementación. OBJETIVO: Comparar el desempeño clínico y los resultados oncológicos de dos modalidades de tratamiento neoadyuvante del cáncer de recto: terapia neoadyuvante total de corta duración versus quimioradiación. estándar. DISEÑO: Cohorte retrospectivo. AJUSTE: Centro oncológico designado por el NCI. PACIENTES: Un total de 413 cánceres rectales localmente avanzados diagnosticados entre junio de 2009 y mayo de 2018 que recibieron cualquiera de los regímenes neoadyuvantes. INTERVENCIONES: Hubo 187 pacientes tratados con terapia neoadyuvante total de ciclo corto (radiación 5 × 5 Gy seguida de quimioterapia de consolidación basada en oxaliplatino) en comparación con 226 pacientes de quimiorradiación (aproximadamente 50, 4 Gy de radiación en 28 fracciones con equivalente de fluorouracilo concurrente). PRINCIPALES MEDIDAS DE RESULTADO: Los criterios primarios de valoración fueron la disminución del estadio del tumor, medido por la respuesta completa y las tasas de puntuación rectal neoadyuvante "baja", y la supervivencia libre de progresión. Los análisis secundarios incluyeron las características del tratamiento y las tasas de finalización, conservación del esfínter y recurrencia. RESULTADOS: La terapia neoadyuvante total de corta duración, se asoció con tasas más altas de respuesta completa (26, 2% versus 17, 3%, p = 0, 03) y puntuaciones rectales neoadyuvantes "bajas" (40, 1% versus 25, 7%, p < 0, 01) a pesar de una mayor carga de enfermedad con ganglios positivos (78, 6% versus 68, 9%, p = 0, 03). Los pacientes de ciclo corto también completaron el tratamiento trimodal con mayor frecuencia (88, 4% versus 50, 4%, p < 0, 01) y tuvieron menos meses con estomas temporales (4, 8 versus 7, 0, p < 0, 01). Ambos regímenes lograron un control local comparable (recidiva local: 2, 7% de SC-TNT versus 2, 2% de TRC, p = 0, 76) y supervivencia libre de progresión a 2 años (88, 2% de SC-TNT [IC: 82, 9 - 93, 5] versus 85, 6% CRT [CI: 80, 5 - 90, 7]). LIMITACIONES: Diseño retrospectivo, gravedad de la enfermedad desequilibrada y dosificación variable de quimioterapia neoadyuvante de consolidación. CONCLUSIONES: La terapia neoadyuvante total de ciclo corto se asoció con una mejora en la reducción del estadio y una supervivencia libre de progresión similar en comparación con la quimioradiación. Estos resultados se lograron con ciclos de radiación más cortos, tratamientos mejor finalizados y menos tiempo en ostomías de derivación. La terapia neoadyuvante total de corta duración es un régimen óptimo para el cáncer de recto localmente avanzado. Consulte Video Resumen en http://links.lww.com/DCR/B724 . ( Traducción- Dr. Fidel Ruiz Healy )